The Dynamic Relationship between Innate Immune Biomarkers and Interferon-Based Treatment Effects and Outcome in Hepatitis C Virus Infection Is Altered by Telaprevir - Malone, David F. G.; Falconer, Karolin; Weiland, Ola; Sandberg, Johan K. (PloS one, 2014)
Soluble CD14 (sCD14) and IL-18 are markers and mediators of the innate immune response, and their plasma levels candidate biomarkers of HCV treatment effects and outcome. Here, we retrospectively studied sCD14 and IL-18 over the course of interferon-based treatment of HCV genotype 1 infection, with the aim to investigate the impact of direct-acting antivirals (DAAs) on the dynamics and relationships between these biomarkers and treatment effects and outcome. Two cohorts were followed longitudinally; one treated with standard dual therapy of pegylated IFNα and ribavirin, and one cohort receiving triple therapy including Telaprevir. sCD14 and IL-18 were measured before and during treatment and analyzed in relation to treatment effects. The initial analysis confirmed two patterns previously observed in patients with HCV/HIV-1 co-infection: Baseline levels of sCD14 were significantly lower in patients that went on to clear HCV infection in response to IFNα and ribavirin, and sCD14 levels were strongly induced during the course of this treatment. Interestingly, baseline levels of sCD14 and IL-18 in combination predicted treatment outcome in dual therapy better than either marker alone. Notably, these associations were weaker with the addition of Telaprevir to the treatment regimen, suggesting that the relationships between innate immune activation and outcome were altered and diminished by inclusion of a DAA in the treatment. In triple therapy, the dynamic increase of sCD14 in response to treatment was higher in patients clearing the virus, suggesting that the innate response to interferon is still significantly associated with outcome in patients treated with DAA-containing regimens. These results support the notion that levels of innate immune activation before and during treatment are associated with interferon-based treatment outcome. Furthermore, the addition of Telaprevir significantly alters the dynamics and relationships between innate immune biomarkers and treatment effects and outcome.